Action based research for capacity building of neighbourhood communities (EAAE Annual Conference Proceedings, 2023)
This paper aims to present action research experiences in Romanian context and reflection on architectural education contribution to helping neighbourhood communities. The project entitled Urban Education Live - Innovative Urban Education in Live Settings - meant applying social mapping tools with a civic initiative group and then defining a common agenda that was presented to the local authorities as the first neighbourhood development plan in Romania.